The Determinants of Farmers' Technical Efficiency in Corn Production: Empirical Evidence from Jambi Province. Issue 1 (1st October 2022) - Edison
Abstract: The various levels of production will reflect uncertainty and risk factors in corn farming. The main problem in corn farming is that the productivity level is still low. This low level of productivity is due to farmers' limited ability to allocate inputs such as seeds, fertilizers, and appropriate pesticides in peat land. This study aimed to estimate technical efficiency and its determinants in corn production in Jambi Province, Indonesia. In this study, 2020 corn planting season data were used. A sample of 120 corn farmers was taken randomly by the stratified random sampling technique based on cross-sectional data that were collected in 2021. The Cobb-Douglas stochastic frontier production function with incorporation of inefficiency effects was employed to analyze the data. According to the results, the technical efficiency rate ranged from 63.46% to 99.54%, with an average of 74%. The significant factors found to positively affect corn yield were seed quantity, potash fertilizer, labor, and corn variety. Meanwhile, nitrogen fertilizer and pesticide were negatively related to corn yield. The significant determinants of technical efficiency that were positively related to technical inefficiency included educational attainment, training, credit access, and household labor